Perception of product sustainability : the case of processed tomatoes – A qualitative study in Germany - Carolin Groth and Christoph Wegmann and Stephan Meyerding (Journal of Retailing and Consumer Services, 2023)
One way to slow down climate change is to help consumers to make more sustainable decisions. The food system accounts for up to one third of greenhouse gas emissions. To ensure consumers can make more sustainable food choices they need to have the necessary knowledge to do so. But consumer perception of the sustainability of food product characteristics might differ from results of greenhouse gas emissions or other environmental impacts in a life-cycle assessments of food products. The aspects of sustainability that are estimated incorrect by consumers need to be identified, so that the necessary knowledge to make more sustainable choices can be provided. To gain insights into consumer perception of the sustainability of food product characteristics, using the example of processed tomatoes, we conducted a qualitative study in Germany using focus group discussion. Ten young consumers, aged between 18 and 37, participated. Millennials and consumers from Generation Z were selected as they are considered to be crucial to a change towards more sustainable food production in the future. The focus group discussion was analyzed using the qualitative summarizing content analysis according to Mayring. The main findings indicate that consumers overestimate the sustainability of glass packaging and regional production. In contrast, consumers underestimate the emissions from heated greenhouses and the sustainability of composite boards and plastic packaging. The study shows that consumers are misinformed regarding sustainability of food product characteristics, such as production systems, packaging, and origin and that there is a need to better inform consumers, so that they have the knowledge to make more sustainable food choices.